Intensi Berwirausaha Mahasiswa Ditinjau dari Sikap, Norma Subjektif, dan Persepsi Kontrol Perilaku - Sri Utami (LANCAH: Jurnal Inovasi dan Tren, 2026)
This study analyzes the effects of attitude toward entrepreneurship, subjective norms, and perceived behavioral control on students' entrepreneurial intention. The study used a quantitative explanatory design involving 205 students from the Department of Accounting Science, Universitas Negeri Makassar. Respondents were selected through purposive sampling based on three criteria: active student status, completion of an entrepreneurship course, and willingness to complete the questionnaire. Data were collected using a closed-ended questionnaire with a five-point Likert scale and analyzed using multiple linear regression. The results show that attitude toward entrepreneurship has a positive and significant effect on entrepreneurial intention (β = 0.203; p < 0.001), subjective norms have a positive and significant effect (β = 0.212; p < 0.001), and perceived behavioral control has a positive and significant effect (β = 0.382; p < 0.001). Together, the three variables explain 45.6% of the variance in entrepreneurial intention. Perceived behavioral control is the strongest predictor, indicating that students' entrepreneurial intention is closely related to confidence in managing business tasks, risks, and opportunities.